Kurikulum Pelajar Pancasila dan Nilai Lokal di SMP Darul ‘Ulum 1 Unggulan Jombang - Luluk Firdausiyah (ALSYS, 2025)
The limited comprehensive studies on the integration of the Kurikulum Profil Pelajar Pancasila (KPPP) with local values at the junior high school level—particularly in high-performing schools with strong religious characteristics—forms the background of this research. This phenomenon warrants critical examination due to its significant implications for shaping holistic student character rooted in national culture and adaptable to global challenges. This study aims to analyze the strategies for implementing KPPP, identify forms of local value integration, and explore the perceptions and lived experiences of stakeholders at SMP Darul ‘Ulum 1 Unggulan Jombang. A qualitative method with an interpretive phenomenological approach was employed to uncover the subjective meanings and real experiences of teachers, students, and school management. The findings indicate that KPPP implementation is carried out through problem-based projects and extracurricular activities, while local values are explicitly integrated into local content subjects and implicitly reinforced through a school culture emphasizing religiosity and nationalism. These findings align with Vygotsky’s social constructivist theory, which underscores the role of social and cultural interaction in value formation, and support the contextual education approach. The study concludes that the success of KPPP implementation and local value integration is influenced by school leadership commitment, teachers’ pedagogical competence, and active community involvement. Theoretically, this study contributes to the literature on character education rooted in local wisdom, and practically, it recommends the development of a contextualized KPPP guide and the optimization of local values across other schools.